2007
DOI: 10.1007/s11010-007-9432-7
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropic regulation of circadian clockwork in rat granulosa cells

Abstract: The circadian clock is responsible for the generation of circadian rhythms in hormonal secretion and metabolism. These peripheral clocks could be reset by various cues in order to adapt to environmental variations. The ovary can be characterized as having highly dynamic physiology regulated by gonadotropins. Here, we aimed to address the status of circadian clock in the ovary, and to explore how gonadotropins could regulate clockwork in granulosa cells (GCs). To this end, we mainly utilized the immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 35 publications
3
63
0
Order By: Relevance
“…We concluded that circadian clockwork in ovarian cells is affected during cellular differentiation. Another study illustrated that both follicle-stimulating hormone (FSH) and LH exerted diverse specific functions on the clockwork of granulosa cells in vitro as proved by Per2 oscillations (25). Consistent with the above two reports (24,25), a study demonstrated that endocrine signals, FSH, and LH are able to transmit phase information to the ovaries and cultured ovarian cells in vivo and in vitro (72).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…We concluded that circadian clockwork in ovarian cells is affected during cellular differentiation. Another study illustrated that both follicle-stimulating hormone (FSH) and LH exerted diverse specific functions on the clockwork of granulosa cells in vitro as proved by Per2 oscillations (25). Consistent with the above two reports (24,25), a study demonstrated that endocrine signals, FSH, and LH are able to transmit phase information to the ovaries and cultured ovarian cells in vivo and in vitro (72).…”
mentioning
confidence: 60%
“…Over the past decade, accumulating evidence has demonstrated that functional circadian clockwork exists in mammalian ovaries (8,11,12,16,25,31,42,52,72). Originally, Fahrenkrug et al (16) showed that rat ovaries displayed a circadian expression of the clock genes Period (Per) 1 and Per2.…”
mentioning
confidence: 99%
“…2, B & C). Conversely, a few robust oscillations were detected in the granulosa cells from antral follicles, albeit with a continuous decreasing of amplitude (He et al, 2007a). FSH was also effective at inducing the oscillation seen at approximately 24 h (Fig.…”
Section: Circadian Rhythm In Ovarian Cells Under Hormonal Stimulationmentioning
confidence: 85%
“…The circadian clock system may contribute to the progress of follicular development, luteinization and luteolysis, and steroid hormone-induced proliferation and differentiation of uterine cells through fluctuating hormones. Recently, there is a growing body of evidence that circadian clock genes are expressed in reproductive tissues including the ovary and uterus (Johnson et al, 2005;Nakamura et al, 2005;Fahrenkrug et al, 2006;Dolatshad et al, 2006;Karman & Tischkau, 2006;He et al, 2007aHe et al, , 2007bHe et al, , 2007cNakao et al, 2007;Hirata et al, 2009;Sellix & Menaker, 2010;Uchikawa et al, 2011). Many regulatory elements are located at the upstream of clock genes, such as steroid hormone response element half-sites and the adenosine 3',5'-cyclic monophosphate (cAMP) response element site as well as E-box and D-box elements.…”
Section: Introductionmentioning
confidence: 99%
“…52 The same study provided evidence for a gonado tropinmediated regulation of clock gene expression in the ovaries, as FSH acutely induced Per1 expression in granulosa cells in vitro with a peak within 1 hour. A similar induction was found after the administration of LH in mature granulosa cells, and both FSH and LH seemed to be able to synchronize the circadian rhythm in granulosa cells.…”
mentioning
confidence: 80%